Faktor-Faktor Penyebab dalam Penerbitan Sertifikat Asli Tapi Palsu pada Kantor Pertanahan Kota Jayapura - Palenewen, James Yoseph (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2023)
This research aims to find out the factors that cause the issuance of Original But Fake Certificates at the Jayapura City Land Office and to find out how to cancel Original But Fake Certificates or legally defective certificates at the Jayapura City Land Office. The approach method used in this research is the normative juridical approach, namely an approach that refers to laws, library materials, written regulations or other secondary legal materials. The results of this research reveal that the factors that cause the issuance of genuine but fake certificates at the Jayapura City Land Office are 2 (two) main things, namely the first is from the applicant himself with dishonesty by making fake documents from blank signatures to the parties involved. adjacent to the land, in other words it can be said that the applicant from the start had bad intentions with the intention of deceiving the land office by entering false data, secondly from the Land Office itself because of administrative legal defects such as procedural errors, errors in applying regulations. legislation, errors in the subject of rights, errors in types of rights, area calculation errors, overlapping land rights, incorrect juridical data or physical data or other errors of an administrative nature and how to cancel Original but Fake Certificates or legally defective certificates at the Office Jayapura City Land Affairs can be carried out by means of an application by the party concerned with a court decision which has permanent legal force.